Increased expression of complement components in tuberous sclerosis complex and focal cortical dysplasia type 2B brain lesions. Issue 2 (14th December 2021) - Gruber, Victoria‐Elisabeth; Luinenburg, Mark J.; Colleselli, Katrin; Endmayr, Verena; Anink, Jasper J.; Zimmer, Till S.; Jansen, Floor; Gosselaar, Peter; Coras, Roland; Scholl, Theresa; Blumcke, Ingmar; Pimentel, José; et al.
Abstract: Objective: Increasing evidence supports the contribution of inflammatory mechanisms to the neurological manifestations of epileptogenic developmental pathologies linked to mammalian target of rapamycin (mTOR) pathway dysregulation (mTORopathies), such as tuberous sclerosis complex (TSC) and focal cortical dysplasia (FCD). In this study, we aimed to investigate the expression pattern and cellular distribution of the complement factors C1q and C3 in resected cortical tissue of clinically well‐characterized patients with TSC and FCD2B. Methods: We applied immunohistochemistry in TSC ( n  = 29) and FCD2B ( n  = 32) samples and compared them to autopsy and biopsy controls ( n  = 27). Furthermore, protein expression was observed via Western blot, and for descriptive colocalization studies immunofluorescence double labeling was performed. Results: Protein expression for C3 was significantly upregulated in TSC and FCD2B white and gray matter lesions compared to controls. Staining of the synaptic vesicle protein synaptophysin showed a remarkable increase in the white matter of both TSC and FCD2B. Furthermore, confocal imaging revealed colocalization of complement factors with astroglial, microglial, neuronal, and abnormal cells in various patterns. Significance: Our results demonstrate that the prominent activation of the complement pathway represents a common pathological hallmark of TSC and FCD2B, suggesting that complement overactivation may play a role in these mTORopathies.